Analisis Nilai Impedansi Listrik pada Daging Ikan Nila yang Disimpan dalam Lemari Es - Rizka Rahmatie Agusta Putri; Chomsin Sulistya; Didik R Santoso (Department of Physics, Sebelas Maret University, 2017)
Electrical impedance value analysis on frozen tilapia flesh aims to analyze non-destructive method of electrical impedance to distinguish between fresh and frozen tilapia flesh. The measurements were carried out to measure electrical impedance fresh tilapia flesh and frozen tilapia flesh for 1-5 days at 10 Hz - 200 kHz frequency using needle electrode. The result shows that the impedance value characteristics of the fresh tilapia flesh is higher than frozen tilapia flesh. The longer strored in the freezer is directly reversed with the value of electrical impedance. The observation of electrical impedance on quality of tilapia flesh preferable observed at a frequency of 1 kHz - 100 kHz.